Three-dimensional kinematic analysis of the snatch of elite Greek weightlifters - Gourgoulis, V.; Aggeloussis, N.; Mavromatis, G.; Garas, A. (Journal of Sports Sciences, 2000)
We investigated the linear kinematics and the change in energy of the barbell and the angular kinematics of the trunk and leg during the snatch technique of 12 elite male Greek weightlifters under competitive conditions after the new weight classification. Two S-VHS cameras operating at 60 Hz were used to record the lifts. The spatial coordinates of selected points were calculated using the direct linear transformation procedure; after digital filtering of the raw data, the angular displacements and angular velocities were calculated for the hip, knee and ankle joints. The following variables were also calculated for the barbell: vertical and horizontal displacement, vertical linear velocity and acceleration, external mechanical work and power output. The results revealed that all weightlifters flexed their knees during the transition phase, independently of their weight category. This indicates that the athletes use the elastic energy produced during the stretch-shortening cycle to enhance their performance. In nine athletes, we found that the barbell trajectory did not cross a vertical reference line that passed through the initial position of the barbell. The vertical linear velocity of the barbell was increased continuously from the beginning of the movement until the second maximum extension of the knee joint, with no notable dip being observed. Regarding the change in energy of the barbell, we found that the mechanical work for the vertical displacement of the barbell in the first pull was significantly greater than the mechanical work in the second pull. In contrast, the estimated average mechanical power output of the athletes during the vertical displacement of the barbell was significantly greater in the second pull than in the first pull. We conclude that the major elements of the snatch technique of elite Greek weightlifters have not been aff ected by the new weight classification.